Exploring Independence Values through Character Development in the Luck Movie - Kharisa Aprilia Fiandita; Endah Alamsari Andayani; Yuliyanto Sabat (Jambura Journal of English Teaching and Literature, 2026)
This study examined how the animated film "Luck" depicted independence. The protagonist of the tale was Sam Greenfield, a young lady who initially had little luck. As the narrative progresses, she develops self-reliance, makes wise choices, and overcomes obstacles. While moral messages in animated films have been the subject of some prior studies, independence as a fundamental ideal has received less attention. The purpose of this study was to investigate how Sam's choices, behaviors, and personal development demonstrate independence principles. A qualitative descriptive method was employed in the study. By watching the film and identifying key moments, dialogue, and character actions, they gathered information. The data was arranged into four primary categories that demonstrated independence: being independent and in charge, making wise decisions, exhibiting bravery and perseverance, and developing via self-discovery. The findings demonstrated that Sam's independence comes from acting independently, making deliberate choices, displaying emotional fortitude in trying circumstances, and discovering more about herself via her experiences. According to the study, independence is a multifaceted trait that is cultivated via diligence, thorough consideration, and perseverance. Additionally, it was believed that pupils could learn valuable life skills from animated films, such as independence and self-reliance.